2012
DOI: 10.4236/ajac.2012.312104
|View full text |Cite
|
Sign up to set email alerts
|

Acylhydrazide and Isatin Schiff Bases as Alternate UV-Laser Desorption Ionization (LDI) Matrices for Low Molecular Weight (LMW) Peptides Analysis

Abstract: Matrix-assisted laser desorption/ionization (MALDI) is a preferred and widely used mass spectrometric technique for the analysis of macromolecules. Limited UV-LDI matrices are available for the analysis of biomolecules due to the restricted structural features to serve in the laser desorption/ionization mechanism with a problem of background signals appearing in the low mass region. This paper describes the application of Schiff base derivatives of acylhydrazide and isatin as alternate UV-LDI matrices for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…For the applications and biological activity of Schiff bases, see: Musharraf et al (2012); Khan et al (2012). For the crystal structures of related compounds, see: Taha et al (2012a,b); Naz et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…For the applications and biological activity of Schiff bases, see: Musharraf et al (2012); Khan et al (2012). For the crystal structures of related compounds, see: Taha et al (2012a,b); Naz et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…The (E)-4-((6-chloro-2-oxoindolin-3-ylidene)methyl)benzohydrazide was treated with different acetophenones and aryl aldehydes in the presence of acetic acid to give desired products (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Scheme-2. …”
Section: Scheme-1mentioning
confidence: 99%
“…Benzohydrazides are easily converted into hydrazones by treating with aldehyde or ketone [4]. Benzohydrazones are applicable in mass spectrometry as alternate UV-LDI matrices for the analysis of peptides with significantly low background signals [5]. Recent studies on benzohydrazones also showed that they are potent antileishmanial [6] antioxidant [7,8] antidiabetic [9,10] antibacterial [3] and antifungal [11] agents.…”
Section: Introductionmentioning
confidence: 99%